Refleksi Nilai Pendidikan Karakter dalam Cerita Rakyat Abu Nawir - Nofrahadi, Nofrahadi; Rafdisyam, Rafdisyam; Mohamad, Hafrison; Eka Amelia, Rezky; Sohnui, Suhailee (GERAM, 2024)
The purpose of this study is to identify and interpret the values of character education in a folklore entitled Abu Nawir. Character education is an effort to help the growth and development of the inner and outer souls of the younger generation from their innate characteristics towards a society full of compassion. Reflections of character education values contained in folklore are used as "train carriages" that can lead the younger generation of Indonesia to a better future. Today, there are many cases of moral decline. This is because the younger generation is unable to filter the negative influence of social media in the current technological era. This study uses a qualitative descriptive method. This study uses research data in the form of words, phrases, clauses, and sentences. The data source in this study comes from the Abu Nawir story text. The reading and note-taking technique is the data collection technique used. The interactive technique is the data analysis technique used, namely reducing data, presenting data, and drawing conclusions. The findings of this study show that there are nine values of character education, namely discipline, hard work, democracy, independence, curiosity, social concern, friendship or communicative, love of peace, and responsibility.